Early Childhood Caries in Peru - Castillo, Jorge L.; Palma, Camila; Cabrera-Matta, Ailín (Frontiers in Public Health, 2019)
Early Childhood Caries is a global oral health problem, and Peru may be one of the countries with the highest prevalence of untreated ECC in South America. The purpose of this study is to perform a comprehensive literature review of Peruvian published data regarding early childhood caries (ECC), in order to depict an epidemiological profile. ECC prevalence, risk factors, its impact on child development, as well as public oral health interventions so far have been included in this review. The results demonstrate extremely high ECC levels in Peruvian scholars, as well as significant oral health disparities. Regarding risk factors, poverty, high sugar consumption, and low oral health literacy seem to be key in caries development. However, the number of studies is limited and their quality equivocal. It seems adequate to say that public health policies have not prioritized oral health. However, in recent years, new regulations and evidence-based documents like the first Clinical Practice Guideline for the prevention, diagnosis and management of caries in children, the Guideline for Children’s healthy Growth and Development, the Law on Healthy Diet, and the Manual on Food Advertising, give us some hope for the future of infants’ oral health in Peru.